Karakeçili Dialect I (Kırıkkale)-Introduction - Serdar YAVUZ (Fırat University, 2019)
Karakeçili Dialect I (Kırıkkale)-Introduction ABSTRACT Since eleventh century, Anatolia has been a Turkish country as a result of migrations of Yoruk and Turkman tribes. Different dialects have appeared as a result of these tribes coming to Anadolu. Forming the source of written language of Turkey Turkish , Anatolian dialects serve as a treasure. Anatolian dialects have great importance in terms of finding equivalents of borrowed words. Works about dialects serve as a limitless source in terms of strategical language researchs. Science of dialectology is mainstay of process of Nations’ presence and of corelating between past and today. This work is a dialectology research for Karakeçili town of Kırıkkale province within the scope of basic principles above. Karakeçilis form the backbone of Kayı, founder tribe of Ottoman Empire.